European Association of Urology Guidelines Office Rapid Reaction Group: An Organisation-wide Collaborative Effort to Adapt the European Association of Urology Guidelines Recommendations to the Coronavirus Disease 2019 Era - Ribal, Maria J; Cornford, Philip; Briganti, Alberto; Knoll, Thomas; Gravas, Stavros; Babjuk, Marek; Harding, Christopher; Breda, Alberto; Bex, Axel; GORRG Group; Rassweiler, Jens J; Gözen, Ali S; et al. (European urology, 2020)
The coronavirus disease 2019 (COVID-19) pandemic is unlike anything seen before by modern science-based medicine. Health systems across the world are struggling to manage it. Added to this struggle are the effects of social confinement and isolation. This brings into question whether the latest guidelines are relevant in this crisis. We aim to support urologists in this difficult situation by providing tools that can facilitate decision making, and to minimise the impact and risks for both patients and health professionals delivering urological care, whenever possible. We hope that the revised recommendations will assist urologist surgeons across the globe to guide the management of urological conditions during the current COVID-19 pandemic.
Keywords: Pandemic; Section Offices; Urology; Urologic Diseases; European Association of Urology; Guidelines Office; společnosti lékařské; Europe; Disease Management; koronavirové infekce; Practice Guidelines as Topic; Societies, Medical; Betacoronavirus; pandemie; směrnice pro lékařskou praxi jako téma; SARS-CoV-2; Coronavirus disease 2019; Evropa; virová pneumonie; Guidelines; lidé; Humans; Pneumonia, Viral; Pandemics; Coronavirus Infections; urologie; management nemoci; urologické nemoci; COVID-19